Population fluctuation of rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyralidae) - Salmah, Mohamed; Marina, Roseli; Nur Azura, Adam; Nur Athiqah, Md Yusof; Wei Hong, Lau; Salmah, Yaakop (2015)
—Rice leaffolder, Cnaphalocrocis medinalis is the major insect rice pest in Asian countries. Their occurrence was not successfully controlled and can cause economic yield loss for heavy infestation. Very few studies had been conducted on their life cycle and population fluctuation which are important as baseline knowledge for their control program. Hence, this study was conducted to observe the population fluctuation of C. medinalis and to investigate the relationship of C. medinalis with environmental factors; temperature and relative humidity. Sampling of C. medinalis was carried out weekly for ten weeks from April 12, 2015 which 20 days after sowing (DAS) until June 14, 2015 (83 DAS). The larvae were collected randomly by hand-picking from 10 hills per plot in three 15m x 4m plots from 0800 – 1100 hours. Population of C. medinalis was observed as early as 20 DAS and continue with similar pattern with no significant difference (P>0.05) until 48 DAS. The highest population was during 62 DAS with mean population 4.3 larvae per 10 hills which significantly different (P<0.05) with other weeks except with 55 DAS with mean population 4.0 larvae per 10 hills. Leaves at this plant stage were found to be most favourable to all larval instars. However, during last three weeks (69-83 DAS), there was no C. medinalis found as the plant stage at 69-83 DAS were not favourable for larval consumption. From correlation analysis, the population of C. medinalis were not influenced by temperature and relative humidity